Risiko Pembiayaan Murabahah, Mudharabah dan Musyarakah BUS Terhadap Profitabilitas (ROA) Periode 2011-2015 - Yulianah Yulianah; Euis Komariah (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2017)
The purpose of this research is to examine the effect of financing murabaha, mudaraba and musharaka risk on profitability. This research used the sample of sharia banks in Indonesia during 2011-2015 period and used multiple linear regression analysis method. The number of sharia banks that were became in this research were 6 sharia banks. The result of this research indicates that only financing murabaha risk influences on profitability parially, while the risks of financing mudharaba and musharaka no influences on profitability partially. The risks of financing murabaha, mudharaba and musharaka influences on profitability simultaneously.